Efficacy of percutaneous closure of patent foramen ovale: comparison among three commonly used occluders. Issue 5 (4th February 2011) - Thaman, R; Faganello, G; Gimeno, J R; Szantho, G V; Nelson, M; Curtis, S; Martin, R P; Turner, M S
Abstract : Background: Percutaneous closure of patent foramen ovale (PFO) is standard treatment for patients with paradoxical embolism but studies examining the efficacy of the various occluders are lacking. Objective: To evaluate short- and medium-term closure rates of three common occluders. Methods: One hundred and sixty-six adults (47±12 (18–81 years)) were evaluated with transthoracic bubble echocardiography before and after PFO closure. Only patients with large PFOs were included (>30 bubbles in the left heart after Valsalva). Results: Three occluders were used: Amplatzer (AGA Medical Corporation) (n=80, 48%), Gore Helex (n=48, 29%) and Premere TM (St Jude Medical) (n=38, 23%). One (0.6%) neurological event occurred during follow-up. At 6 months significant residual shunting after Valsalva was highest in the group that received the Helex (58.3%), and lower for Premere (39.5%) and Amplatzer (32.5%). At final follow-up residual shunting remained higher in patients with the Helex (33.3%) than in Premere (18.5%) and Amplatzer (11%). Amplatzer had a significantly lower residual shunt rate than Helex (p<0.05 at 6 months and final follow-up). The Premere had an intermediate residual shunt rate. Septal aneurysm also predicted residual shunting (RR=24.7, 95% CI: 8.2 to 74.4, p<0.0001). Conclusions: Percutaneous PFO closure is an efficacious progressive treatment but closure rates also depend on the presence of aneurysm and differ between occluders.